Accounts payable : a guide to running an efficient department - Schaeffer, Mary S. (Wiley, 2004)
The Accounts Payable Department is the department responsible for paying outside vendors for goods or services that have been purchased by a corporation. This book will take a look at the responsibilities that traditionally fall under the accounts pay-able umbrella along with the innovative issues now facing the field.